2016
DOI: 10.1063/1.4960023
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionless size scaling of intrinsic rotation in DIII-D

Abstract: A dimensionless empirical scaling for intrinsic toroidal rotation is given; M A~βN ρ *, where M A is the toroidal velocity divided by the Alfvén velocity, β N the usual normalized β value, and ρ* is the ion gyroradius divided by the minor radius. This scaling describes well experimental data from DIII-D, and also some published data from C-Mod and JET.The velocity used in this scaling is in an outer location in minor radius, outside of the interior core and inside of the large gradient edge region in H-mode co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(97 reference statements)
2
6
0
Order By: Relevance
“…Although the indications of this experiment are that the fast-ions may have contributed to the discrepancy between the dimensionless parameter scan and database results, a direct comparison between the ρ * scaling of intrinsic Mach number at the top of the pedestal and database studies shows some discrepancy still remains. While [23,24] found the Alfvén Mach number to scale as ρ 1 * , the present results shows a scaling of ρ 0 * , which agrees with the older result of [14]. Note that in a dimensionless parameter scan, Mach number and Alfvén Mach number have the same scaling to the extent β has been held constant.…”
Section: ρ * Scaling Of Intrinsic Rotationsupporting
confidence: 86%
See 3 more Smart Citations
“…Although the indications of this experiment are that the fast-ions may have contributed to the discrepancy between the dimensionless parameter scan and database results, a direct comparison between the ρ * scaling of intrinsic Mach number at the top of the pedestal and database studies shows some discrepancy still remains. While [23,24] found the Alfvén Mach number to scale as ρ 1 * , the present results shows a scaling of ρ 0 * , which agrees with the older result of [14]. Note that in a dimensionless parameter scan, Mach number and Alfvén Mach number have the same scaling to the extent β has been held constant.…”
Section: ρ * Scaling Of Intrinsic Rotationsupporting
confidence: 86%
“…As explained in that work, these results were unexpected based on concepts of residual stress driven intrinsic rotation and results from database studies of intrinsic rotation, which found the intrinsic rotation at the top of the pedestal to scale as ρ 0 * [14] or ρ 1 * [23,24]. The results of [25,26] also show a scaling of ρ 1 * if L φ ∼ a, where L φ is the radial scale length of electrostatic fluctuation intensity.…”
Section: ρ * Scaling Of Intrinsic Rotationmentioning
confidence: 80%
See 2 more Smart Citations
“…Ion orbit loss has also been used to model the toroidal angular momentum (TAM) transport and toroidal rotation at the outboard of diverted tokamaks [6,15,16,17,18,19,20,21,22]. Consider ion orbits at the outboard midplane; ions with parallel velocity in the direction of toroidal plasma current (denoted by "co-current") drift radially inwards, while ions with oppositely directed parallel velocity (denoted by "counter-current") drift radially outwards (figure 1).…”
Section: Introductionmentioning
confidence: 99%